THE ANTIBIOTIC RESISTANCE AND THE ABILITY OF BACTERIATO PRODUCE -LACTAMASES - Mashuri Masri; Joko Widodo; Ekafadly Jusuf; Delima Engga Maretha; Wahyuni Wahyuni (Prosiding Seminar Nasional Biotik, 2022)
Background : Accessibility of bacterial patterns and their sensitivity to pus can be utilized as a thought in giving anti-microbials observationally. Vale Sorowako Inco Hospital was located in mining region where health services were not as enormous as in huge cities but can still carry out free sensitivity tests without send them to a referral hospital. Methods: Antibiotics (Penicillin, cefuroxime, Ceftriaxone, and meropenem) were tried by dise diffusion. The suspension of the test microscopic organisms was included with NaCL 0.85% until it reaches turbidity, at that point a stick sterile cotton swab of bacterial suspension on the MHA (Muller Hinton Agar) media,  paper disks containing the antibiotics were put on the media and incubated for 24 hours. Results: Staphylococcus aureus, Enterobacter cloacae, Enterobacter aerogenes, Acinetobacter baumannii, Pseudomonas aeruginosa, Serratia odorifera, and Aeromonas hidropila were bacteria isolated from pus. S. aureus and E. cloacae were the most (25%).  Meropenen is the most sensitive antibiotics  (90%), Penicillin and Cefuroxime are the most resistance (45%). Conclusions : The resistance that happens at Vale Sorowako Inco Hospital is not due to a prescription without a culture test ask, since antibiotics given by clinicians are continuously based on a culture test, but since of the capacity of bacteria to produce b-lactamases and the the presence of genes that can code for b-lactamases which moreover cause bacteria to resistant to antibiotics.